Turkish elementary school students' images of scientists - Kaya, Osman Nafiz; Dogan, Alev; Ocal, Erdinc (Ani Yayincilik, 2008)
Problem Statement: Since 1957 there has been a growing body of research related to how students perceive scientists. Results of these studies show that many students perceive scientists as an old male with eyeglasses, wearing a lab coat, and performing dangerous laboratory experiments. This kind of perception may negatively affect students' understanding of science, their tendency of having a science-related career and becoming a scientist. Students' understanding of how scientific knowledge is constructed and their concepts of nature of science have just been added to the major goals of science and technology education in the last elementary education reform carried out in Turkey. Accordingly, Turkish elementary school students (K-8) first need to have an accurate image of scientists in order to acheive these new educational goals. Purpose of Study: The aim of this study was to determine Turkish middle grade students' images of scientists and how students' perceptions differed with respect to the grade levels. Methods: This research was a qualitative study. The population of the study was 6(th), 7(th), and 8(th) grade students in Ankara in the 2005-2006 academic year. The sample for this study consisted of 304 students who were randomly selected from four public schools. As a data collection tool, the Draw-a-Scientist Test (DAST) was used. Findings and Results: Analyses of the students' drawings indicated that most of the students had a stereotypical male scientist image with eyeglasses, wearing lab coats: individuals who work in laboratories. This image of the scientist was parallel to the students' stereotypical images of scientists in the previous studies. However, there was a noticeable difference between the results of this study and the earlier studies, including some students' drawing scientists with smiling faces, wearing ties, and working in gardens. The results of the study also revealed that there were some differences in regard to the grade levels. The reasons for the students' images, which are incorrect or incomplete in many respects, may be that they are getting wrong information through the mass media, particularly from TV programs, and missing the explicit educational goals focusing on developing students' images of scientists in Turkish science curriculum, and of the needed teaching-learning environment. Recommendations: Reasons for students' images of scientists should be investigated. Also, there is a need to carry out studies to help elementary school students develop an accurate image of scientists involving science and technology education.
Keywords: scientist; students' images of scientists; elementary school students; elementary science education